Peningkatan Keterampilan Bermain Drama melalui Teknik Pembelajaran Peran Bergilir pada Siswa Kelas VIII 4 UPT SMP Negeri 3 Alla Kabupaten Enrekang Tahun 2021 - Kasau Kasau (CV. Syntax Corporation Indonesia, 2022)
This Classroom Action Research aims to find out how the rotating role learning technique can improve the drama playing skills of class VIII-4 UPT SMP Negeri 3 Alla, Enrekang Regency. This research is a classroom action research conducted in two cycles. Each cycle consists of four stages, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. This research was conducted collaboratively between researchers and Indonesian teachers. The subjects of this study were students of class VIII-4 UPT SMP Negeri 3 Alla, Enrekang Regency, and the object of this research was the students' drama playing skills using the rotating role technique. Data collection was obtained through observation, field notes, drama playing practice tests, and interviews. Data analysis was carried out using qualitative descriptive techniques supported by quantitative data. The results showed that the use of rotating roles learning techniques was able to improve the drama playing skills of class VIII-4 UPT SMP Negeri 3 Alla, Enrekang Regency. Based on field notes and observation guidelines, there was a change in students in a positive direction. The improvement of drama playing skills is seen from two things, namely the success of the process and the product. The success of the process can be seen from the change in student attitudes after the implementation of the action, students are more active, enthusiastic, dare to express opinions, and are able to work together with other students. The success of the product is seen from the practice test of playing drama. The average value of students' drama play before the implementation of the action was 49.46, the first cycle was 63.5 and in the second cycle was 78.14. The data shows that students' drama playing skills from pre-action to cycle II have increased by 28.68. Some of the aspects that showed the most significant improvement were aspects of expression, movement, and intonation.